Influence of silica nanospheres on the separation performance of thin film composite poly(piperazine-amide) nanofiltration membranes - Li, Qiang; Wang, Yihua; Song, Jie; Guan, Yipeng; Yu, Hui; Pan, Xianhui; Wu, Feiyang; Zhang, Meng (Applied surface science, 2015)
•Poly(piperazine-amide)/silica nanocomposite NF membrane was firstly fabricated.•The addition of silica nanospheres can optimize NF-membrane separation performance.•The silica nanosphere introduced NF membrane exhibits good separation selectivity.•The silica nanosphere introduced NF membrane has superior performance stability. A novel thin film nanocomposite nanofiltration (TFNN) membrane was fabricated by introducing silica nanospheres (ca. 235±11nm) in the interfacial polymerization process of trimesoyl chloride (TMC) and piperazine (PIP) over polysulfone (PS) support for investigating the effect of silica nanofiller on the separation performance (i.e., permeability and salt rejection) of conventional thin film composite poly(piperazine-amide) nanofiltration (TFCN) membrane. The physicochemical characterization results show that all of the silica nanospheres are uniformly embedded on the surface of TFNN membrane. The introduction of silica nanospheres improves the hydrophilicity of the TFCN membrane and also causes its isoelectric point shift to a lower pH value. Moreover, the active poly(piperazine-amide) barrier layer of TFNN membrane (60.8±2.3nm) is thinner than that of the pristine TFCN membrane (72.1±2.5nm) as a control sample. The separation performance tests reveal that the addition of silica nanospheres can obviously elevate the salt rejection of the pristine TFCN membrane from 87.58±0.15 to 94.81±0.17% under 2000ppm of MgSO4 solution and 0.5MPa operating pressure, simultaneously accompanied by the increases of permeate flux from 19.36±0.75 to 22.65±0.68L/m2h. Additionally, compared with pristine TFCN membrane, the fabricated TFNN membrane has relatively low salt rejection (43.20±0.27%) in 0.5MPa operating pressure for 500ppm of NaCl aqueous solution, which demonstrates that the introduction of silica nanospheres can dramatically promote the divalent-ionic separation selectivity. Furthermore, the experimental results suggest that the nanocomposite TFNN membrane possesses stable filtration performance in the softening process of MgSO4 aqueous solution. The separation performance improvement should be attributed to the optimizations of microstructures and surface features of active barrier layer of TFNN membrane, caused by the addition of silica nanospheres.